Ano internacional do esporte e educaçao física: o sistema onu e a pedagogia da hegemonia - Melo, Marcelo Paula de (2018)
International organizations have a relevant pedagogical role in the current capitalist society and the correlation of forces between social classes. The UN System (General Secretariat, its agencies and funds) play major role in this process. The set of issues that mark the neoliberal capitalist project focuses on the sports field and the UN system has to give a prominent role to sports. This resulted in the creation of a series of programs and actions. The substrate of these actions lies in the emergence of principles dear to the neoliberal project in this field